Moderasi Beragama di Tengah Pluralitas Bangsa: Tinjauan Revolusi Mental Perspektif Al-Qur’an - Khalil Nurul Islam (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
Indonesia with its diversity, including ethnicity, culture, tradition, language, to the diversity of religions often lead to conflict due to these differences with various factors surrounding it. Therefore, a progressive step is needed in dealing with diversity issues that can explode at any time and cause huge losses. This study aims to get an understanding and illustration related to the understanding of the concept of religious moderation and the concept of religious plurality in Indonesia, as well as offering solutions through a mental revolution that is very closely related to understanding the concepts of religious moderation and religious plurality itself. The results of this study indicate that religious moderation is closely related to wise attitudes towards religious plurality who his moderation through a mental revolution. Understanding of the concepts of religious moderation and religious plurality must be understood in depth and then realized in the mental revolution movement so as to give birth to acts of mutual respect and tolerance in life in the midst of diversity. Keyword: Religious moderation, Mental revolution, Religious plurality